Temporal population structure of fish communities along the coastal waters of Universiti Malaysia Sabah (UMS) - Amir Syazwan Shawel; John Madin; Ejria Salleh; Mabel Manjaji Matsumoto; Sitti Raehanah Muhamad Shaleh (Researchgate, 2025)
This study examines the temporal pattern of the population structure and community of fish along the coastline of Universiti Malaysia Sabah (UMS), Kota Kinabalu, Sabah. This area is known to have a productive seabed ecosystem to support fisheries, however fishes-related literature is limited and often focusing on specific species rather than communities. The present study fills this gap by providing crucial data on temporal pattern of community species, morphometric size, assemblages and population dynamics of fish caught in fishing net. Findings reveal 61 fish species across 27 families dominated by ponyfish of Leiognathidae including Eubleekeria jonesi, Nuchequula flavaxilla, Photopectoralis bindus and Gazza minuta. The diversity index is significantly (p < 0.05) high in December (H = 2.79) than other months with high contributions of ponyfish species. The smallest size in terms of standard length (SL) and weight (kg) is the species from the Engraulidae family with SL of 7.77 ± 1.46 cm and weigh at 0.007 ± 0.004 kg, in contrast Trichiuridae species is the largest in size with SL of 78.83 ± 25.62 cm and weigh at 0.285 ± 0.095 kg. There are at least two major recruitment peaks annually that linked to the monsoonal season, however natural mortality could cause the loss of nearly 20% populations during early stage while catches and fishing mortality increases drastically as fish grow larger. Fish assemblage and abundance are influenced by water parameters, where Eleuteria Jonesi, Nochebuena nuchals, and Scombroids Tol correlates with high pH, dissolved oxygen, and salinity, while Gazza minute, and Nochebuena Flav axilla with high temperature and turbidity. Continued efforts to monitor fish populations along coastal waters are essential to assess the impacts of human activities while future studies should consider effective fishing gear to optimize catch.